1998
DOI: 10.2307/176832
|View full text |Cite
|
Sign up to set email alerts
|

Conspecific Reproductive Success and Breeding Habitat Selection: Implications for the Study of Coloniality

Abstract: Habitat selection is a crucial process in the life cycle of animals because it can affect most components of fitness. It has been proposed that some animals cue on the reproductive success of conspecifics to select breeding habitats. We tested this hypothesis with demographic and behavioral data from a 17-yr study of the Black-legged Kittiwake (Rissa tridactyla), a cliff-nesting seabird. As the hypothesis assumes, the Black-legged Kittiwake nesting environment was patchy, and the relative quality of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
424
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(437 citation statements)
references
References 49 publications
8
424
5
Order By: Relevance
“…Espmark, Lampe, & Bjerke, 1989;Mundinger, 1982) and breeding site preferences (e.g. Boulinier, McCoy, Yoccoz, Gasparini, & Tveraa, 2008;Brown, Bomberger Brown, & Danchin, 2000;Danchin, Boulinier, & Massot, 1998). However, although this kind of behavioural adjustment can lead to local behavioural convergence (i.e.…”
Section: Do Birds Show Conformity?mentioning
confidence: 99%
“…Espmark, Lampe, & Bjerke, 1989;Mundinger, 1982) and breeding site preferences (e.g. Boulinier, McCoy, Yoccoz, Gasparini, & Tveraa, 2008;Brown, Bomberger Brown, & Danchin, 2000;Danchin, Boulinier, & Massot, 1998). However, although this kind of behavioural adjustment can lead to local behavioural convergence (i.e.…”
Section: Do Birds Show Conformity?mentioning
confidence: 99%
“…As part of a study examining the role of host response in the dynamics of host^parasite interactions (Boulinier et al 1997;Danchin et al 1998), we investigated the presence of maternally transferred antibodies against a microparasite, Borrelia burgdorferi sensu lato, in a spatially structured host^ectoparasite system consisting of the seabird tick Ixodes uriae and the kittiwake Rissa tridactyla. The spirochaete B. burgdorferi is the causative agent of Lyme disease, the most common and medically important vector-borne disease in Europe and the USA (Barbour & Fish 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In each stage, I. uriae attaches to its host for a single, long, blood meal and then returns to the host nesting substrate to overwinter (Eveleigh & Threlfall 1974). It has previously been shown that tick prevalence and abundance are autocorrelated in both space and time at the scale of the host breeding cli¡ (Danchin et al 1998;McCoy et al 1999). As kittiwakes, like many seabirds, are highly philopatric to their breeding sites between years (Coulson & Thomas 1985), ticks become a predictable part of their breeding environment.…”
Section: Introductionmentioning
confidence: 99%
“…We also do not have an understanding of how environmental variability plays into the relationship between calving fidelity and gregariousness-for example, Bathurst calving in 1986 occurred during a later snow melt (Sutherland & Gunn, 1996). Any relationship between calving ground fidelity and gregariousness will be complicated as the cows will be integrating current year's conditions with the previous year's performance on the calving ground (sensu colonial sea-birds which predicate nest site decisions on their previous fledging success and that of their neighbours; Danchin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Increased foraging is likely through reduced vigilance (Ims, 1990;Roberts, 1996;Childress & Lung, 2003;Mooring et al, 2004) and through information from conspecifics' foraging. The cues that conspecifics learn from their neighbours about reproductive success, predators, and resources is termed 'public information' (Danchin et al, 1998;Doligez et al, 2003;2004;Donahue, 2006;Boulinier et al, 2008).…”
Section: Proposed Conceptual Modelmentioning
confidence: 99%